INTERNALISASI NILAI-NILAI KEAGAMAAN MELALUI MEDIA EDUKATIF - Septia Rosalina; Jauharotul Makniyah (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
One of the efforts made by parents diverting children from gadget is to embrace Smart Hafiz as one of the current educational toys and trends supplying positive values to children. Young mothers who have a lifestyle with an updated atmosphere educates their children with sophisticated technology. A very fantastic price is not a problem for parents. The large number of Islamic content offered makes Smart Hafiz able to internalize religious values in children. In addition, Smart Hafiz is also a toy tool that can make children happy. Based on the research context, the focus of the research is to investigate and describe the internalization of religious values in early childhood through Smart Hafiz media, what supporting and inhibiting factors are in internalizing religious values in early childhood through Smart Hafiz media in Karduluk village. The approach used in this research is a qualitative approach with a case study approach. The data collection methods or techniques used are interview, observation, and documentation methods. From this method, the researchers then processed and analyzed to obtain data or information. The informants used are young mothers who owned Smart Hafiz in Karduluk village who put their children into pre-primary education . They know firsthand the scope that this research will undertake. They are considerately aware of various accurate information regarding the problems that occurred in the village of Karduluk. Internalization of religious values in early childhood through the Smart Hafiz media in Karduluk village is carried out by several methods including association / mentoring, habituation, advice, exemplary, and attention / supervision. The supporting and inhibiting factors in internalizing religious values in early childhood through Smart Hafiz media are influenced by several factors, namely Smart Hafiz media, family and the environment.